Complex sphingolipids: Vital determinants of drug susceptibility, membrane integrity and pathogenesis of Candida glabrata. Issue 12 (17th December 2021) - Shahi, Garima; Kumar, Mohit; Khandelwal, Nitesh Kumar; Sarkar, Parijat; Kumari, Sonam; Chauhan, Neeraj; Chattopadhyay, Amitabha; Gaur, Naseem A.; Prasad, Rajendra
Abstract : Complex Sphingolipids (SLs) are unique to fungi, which apart from being novel drug targets, also appear to act as molecular signals, in diverse biological processes. In this study, we have specifically blocked the key synthesis step of SLs metabolism by disruption of the uncharacterized CgIPT1 gene, which based on homology with other Candida spp., predicted to mediate the conversion of MIPC to M(IP)2C. We followed fusion based PCR homologous recombination method for IPT1 deletion by using dominant markerNAT1. The knockout was selected on a nourseothricin drug plate and confirmed by gene specific PCR and by checking M(IP)2C levels. We observed that the specific accumulation of MIPC or lack of M(IP)2C in C. glabrata displayed increased susceptibility to both imidazole's (ketoconazole, miconazole and clotrimazole) and triazoles (fluconazole, itraconazole and posaconazole). RNA Sequencing of Cgipt1Δcells revealed no major impact on of expression levels of common MDR determinants albeit a distinct imbalances in expression of lipid homeostasis genes was evident. The Fluorescence Recovery after Photobleaching (FRAP) experiments confirmed that plasma membrane in Cgipt1Δ cells display a reduction in micro-viscosity leading to increase in drug diffusion and susceptibility of Cgipt1Δcells. Interestingly, the Cgipt1Δ also exhibit attenuated virulence in a murine model. Together, our data confirms the relevance of M(IP)2C in governing drug susceptibility and virulence in C. glabrata .